Analysis of localized muscle fatigue in elderly women with and without a history of falls using electromyographic signal frequency parameters - Silva, Lissara Ellen; Pedroni, Cristiane Rodrigues [UNESP]; Navega, Marcelo Tavella [UNESP]; Scheicher, Marcos Eduardo [UNESP] (Universidade Federal de Santa Catarina, 2014)
One of the problems that most concerns the elderly population is the falling, which can be caused by muscle fatigue. The objective of this study was to compare median electromyographic frequency values for the vastus lateralis muscle and the lateral portion of the gastrocnemius muscle (as parameters of electromyographic fatigue) in elderly people with and without a history of falls. A total of 20 healthy, physically active, elderly women who had or had not suffered falls were enrolled on the study. Median electromyographic signal frequencies were analyzed for the vastus lateralis muscle and the lateral portion of the gastrocnemius muscle in isometric contraction. ANOVA and Student’s t test were used for comparisons, to a cutoff of p ≤ 0.05. Median frequencies for the gastrocnemius and vastus lateralis muscles were both higher in the group with a history of falling, but without statistical significance. It was also observed that the rate of decline in median frequency was greater in the group with a history of falling. It can be concluded that elderly people with a history of falling have a greater tendency to fatigue of the gastrocnemius and vastus lateralis muscles than their peers with no history of falling.

Um dos problemas que mais preocupam a população idosa são as quedas, que podem ser causadas pela fadiga muscular. O objetivo do estudo foi comparar os valores de frequência mediana, como um parâmetro de fadiga eletromiográfica, dos músculos vasto lateral e porção lateral do gastrocnêmio em idosos com e sem história de quedas. Participaram do estudo 20 idosas saudáveis, ativas fisicamente (que sofreram e não sofreram quedas). Analisou-se a frequência mediana do sinal eletromiográfico dos músculos vasto lateral e porção lateral do gastrocnêmio em isometria. As comparações foram feitas pela ANOVA e teste t de Student, considerando p ≤ 0,05. O músculo grastrocnêmio apresentou maiores Fmed no grupo caidor do que no não caidor, o mesmo acontecendo com o vasto lateral, sem significância estatística. Também foi possível observar que a taxa de queda dos valores da frequência foi maior no grupo caidor do que no não caidor. Pode-se concluir que há maior tendência de fadiga dos músculos gastrocnêmio e vasto lateral de idosos caidores.
Análise da fadiga muscular localizada em idosas caidoras e não caidoras através de parâmetros de frequência do sinal eletromiográfico
Keywords: Eletromiografia; Equilíbrio; Equilíbrio postural; Fadiga muscular; Idoso; Senior; Electromyography; Elderly; Balance; Muscle fatigue; Postural equilibrium; Seniors